Sleep and Inflammatory Bowel Disease: An Important Bi-Directional Relationship. Issue 5 (2nd November 2018) - Qazi, Taha; Farraye, Francis A
Abstract: : Sleep deprivation and lack of sleep are a significant public health concern. Several studies have suggested an intricate relationship between sleep, inflammation, and the immune system. Poor sleep has been described well in subjects with inflammatory bowel disease (IBD) and has been linked to disease activity and shown as a predictor for subclinical inflammation and a risk factor for relapse and poorer outcomes. This review describes the relationship between poor sleep, inflammation, and the immune system. Furthermore, the relationship between sleep and IBD are reviewed. The causes of poor sleep in inflammatory bowel disease patient is discussed. Potential therapeutic interventions for the management of common sleep disturbances are provided. :